Rancangan Sistem Irigasi Evaporatif untuk Tanaman Lada - Amalia, Regina; Waspodo, Roh Santoso Budi; Setiawan, Budi Indra (Balai Teknik Irigasi, 2020)
One of the obstacles in providing irrigation water is the difficulty in determining the right parameters to be used in the controlling of timing and amount of irrigation water according to crop needs. One of the alternative parameters that could be considered in order to meet the water needs of plants is the irrigation control based on evaporation. This study aims to produce an evaporative irrigation system design and determine the crop coefficients of pepper. The drip irrigation network consists of a supply tank and distribution pipes that provide water to the plant pots. The network valve opening and closing arrangements are made based on the evaporation in the supply tank. This research was conducted in a plant house for 5 months by observing the observations made on the water balance components, including the rate of evaporation which is measured based on changes in the water level in the water supply tank. The results showed that the evapotranspiration outside the houseplant was greater than that in the plant house. At the beginning of planting pepper, the evapotranspiration was 5.2 mm/day in the plant house and 4.9 mm/day outside. The average evapotranspiration during observation inside the plant house was 4.1 mm/day and 3.8 mm/day outside. Meanwhile, evaporation outside the plant house is smaller than that inside the plant house which ranges from 2-5 mm/day. Provision of water with this evaporative irrigation system of 5.2 mm/day has been able to meet the needs of 4.1 mm/day of evapotranspiration water for pepper plants. The provision of water has been able to encourage the growth of primary branches and flowering. Normal pepper plant growth during this study with calculated crop coefficients ranging from 0.1–0.7.